Scribal tools in ancient Israel : a study of biblical Hebrew terms for writing materials and implements - Zhakevich, Philip, 1983- (History, archaeology, and culture of the Levant., 2020)
"Examines the technology of writing as it existed in ancient Israel. Utilizes the Hebrew Bible as its corpus and focuses on a set of Hebrew terms that designated writing surfaces and writing instruments"--